Exploring Anesthesia Practitioner Perspectives on Post-Spinal Anesthesia Assessment: Implications for Patient Safety and Recovery - Nurdiani, Maria Delviana; Dani Ardian (HM Publisher, 2024)
Post-spinal anesthesia assessment is a critical component of patient care, ensuring the safe and effective recovery of patients following spinal anesthesia. Anesthesia practitioners play a pivotal role in conducting these assessments, yet their perspectives and experiences remain under-explored. This study aimed to investigate anesthesia practitioner perspectives on post-spinal anesthesia assessment, with a focus on identifying factors influencing assessment practices, challenges encountered, and implications for patient safety and recovery. A qualitative descriptive study was conducted, employing semi-structured interviews with anesthesia practitioners involved in post-spinal anesthesia care. Thematic analysis was used to identify key themes and patterns within the data. Anesthesia practitioners emphasized the importance of comprehensive and individualized assessments, considering factors such as patient comorbidities, surgical procedures, and anesthetic agents used. Challenges identified included time constraints, communication barriers, and variations in assessment protocols. Practitioners highlighted the need for standardized assessment tools and improved interdisciplinary collaboration to enhance patient safety and optimize recovery outcomes. In conclusion, this study provides valuable insights into anesthesia practitioner perspectives on post-spinal anesthesia assessment. The findings underscore the importance of addressing challenges and implementing strategies to improve assessment practices, ultimately contributing to enhanced patient safety and recovery following spinal anesthesia.